Serverless Swift Apache OpenWhisk for iOS developers - Sadowski, Marek; Frantzell, Lennart; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2020)
Decrease development time to market with Serverless Swift$1 (Bthe event-based modern architecture for full stack developers. This book reviews how to use the Apache OpenWhisk framework to enrich your standalone applications with cloud-based functionalities from data sources up to Artificial Intelligence. You'll leverage serverless in your mobile apps with use case scenarios and gain the skills that will allow you to create robust, performant, secure yet economically viable systems in a cloud native environment. Finally, you'll see how to participate in the creation and further development of this open source project with Apache Foundation, which is supported by IBM, Google, and others Serverless has become a new style of coding, and it can be used to offload your mobile apps without incurring unnecessary costs. Get a solid, hands-on introduction into serverless, function-as-a-service, and cloud function technologies and learn why startups and enterprises are so excited about using them. You will: Employ Apache OpenWhisk in your apps Expand your iOS skills with Cloud Native Serverless programming Use a Docker container as a Polyglot action.s
Chapter 1: Introducing Serverless -- Chapter 2: Actors in the Serverless Space -- Chapter 3: Apache OpenWhisk - OpenSource Project -- Chapter 4: Hello World from Apache OpenWhisk in Swift -- Chapter 5: Apache OpenWhisk Deep Dive -- Chapter 6 : The Complete iOS App Using Serverless Swift -- Chapter 7: Use Cases -- Chapter 8: Cloud Native Development Best Practices -- Chapter 9 : Conclusions -- Appendix A: Signing up for the IBM Cloud Account.
Keywords: Apple computer; Apple and iOS